Sredstva cestovnog teretnog prometa i uključivanje u tokove EZ - Ivo Županović; Boris Ribarić (Promet - Traffic&Transportation, 1970)
The authors deal with the issues of integration of our road transport i.e. trucking trade into the traffic flows of the EC and discuss the factors of immediate influence upon the increased level of services, as basic factors of discontinuation of further tendency of traffic isolation of our country. If these prerequisites are met there are strong chances for us to successfully join the EC road traffic flows.